Promotional Effect of Tertiary Amine on Asymmetric Catalytic Hydrogenation of Ethyl Pyruvate Over Pt/Al2O3 in Acetic Acid - TAO, GUOZHONG; LU*, GUANZHONG; GUO, YUN; WANG, YANQIN; GUO, YANGLONG (Asian Journal of Chemistry, 2009)
In the asymmetric hydrogenation of ethyl pyruvate over cinchona alkaloid modified Pt/Al2O3 in acetic acid under atmospheric pressure, the enantioselectivity was improved and the reaction rate was accelerated upon addition of tertiary amine. The size of the alkyl substitute in tertiary amine molecule has significant impact on the improvement. Triethylamine is the most effective additive compared with tri-n-butylamine, tri-n-propylamine and trimethylamine. There is an optimum adding amount (0.4 mol/L) of all tertiary amines, at which triethylamine can increase the enantioselectivity of product from 51 to 72 %. The role of tertiary amine in the promotional effect was discussed.